The Role of Public Relations Management in Increasing Community Participation at Madrasah Aliyah Negeri 1 Ciamis - Ramdani, Dede Ahmad; Erihadiana, Mohamad; Syah, Muhibbin (Edumaspul: Jurnal Pendidikan, 2023)
Increasing community participation in MAN 1 Ciamis, the implementation of public relations management in increasing community participation in MAN 1 Ciamis, Evaluation of public relations management in increasing community participation in MAN 1 Ciamis. This research uses a qualitative research approach with descriptive methods and types of field research. Data collection techniques for interviews, observations and documentation. The data analysis technique is to use data triangulation. This research found that 1) Public relations management planning in increasing community participation in MAN 1 Ciamis was carried out through a working meeting tah This research uses a qualitative research approach with descriptive methods and types of field research. Data collection techniques for interviews, observations and documentation. The data analysis technique is to use data triangulation which is carried out annually with all related elements, 2) The implementation of public relations management in increasing community participation in MAN 1 Ciamis refers to the work program that has been determined in the annual work program. This program is divided into two parts, namely routine activities and incidental activities, 3) Evaluation of public relations management in increasing community participation in MAN 1 Ciamis. The Deputy Head of Madrasah for Public Relations also always conducts an evaluation of every implementation of activities, then the results of the evaluation are used as a reference for activities that will be carried out so that they can be better.